Agglomeration economies and clustering: Evidence from German firms - Kurt A. Hafner (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2008)
The paper quantifies the impact of agglomeration economies on the clustering of German firms. Therefore, I use the 2006 Innobarometer survey, which focuses on cluster characteristics and activities of German firms, to empirically identify agglomeration economies derived from the New Economic Geography and Marshall externalities. At the industry specific level, I find that within-industry spillovers are important for German low-tech firms but not for high-tech firms or knowledge intensive firms. At the department level, Marshall externalities such as hiring skilled labor and technological spillover effects are empirically confirmed for some departments like Human Resources or R&D but rarely for others like Production.
Keywords: C20; D21; F12; R12; 330; Agglomeration Economies; New Economic Geography; Externalities; Cluster Analysis; Logistic Regression; Regionale Konzentration; Agglomerationseffekt; Externer Effekt; Neue ökonomische Geographie; Deutschland